The Effect of Transparency and Accountability of the Financial Reports of LAZISMU Yogyakarta on Public Trust in Donating - Farida, Mun; Safitri, Teti Anggita (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
With accountability and transparency of financial reports that are carried out by amil zakat institutions, especially LAZ, this gives the public freedom to evaluate performance and gives trust to Muzakki and the public about what has been carried out by Amil Zakat Institutions. Obstacles that impede the development of zakat institutions in managing zakat funds are due to the problem of the lack of understanding of the community or muzaki in understanding the importance of zakat in shared welfare, as well as the lack of trust in zakat institutions. Low awareness of taxpayers, trust in BAZ and LAZ and Muzaki behavior that is still short-term, decentralized, and interpersonal oriented. The purpose of this study was to determine and analyze the influence of the Transparency and Accountability of LAZISMU's reports on the trust of the people of Yogyakarta City. The analytical method used in this research is descriptive variable to analyze the data by describing the data that has been collected from the respondents' answers to the items in the questionnaire. As well as inferential statistical analysis to show the relationship between the research variables. The data analysis technique used in this study is Multiple Regression Analysis to test whether or not the influence of the two independent variables (X1 and X2) has on the dependent variable (Y). based on the results of the research hypothesis on the variable transparency and accountability of financial statements using the F test has a positive and significant influence on public trust in donating to Lazismu Yogyakarta City.